Religious belief changes among the new generation youth in Thailand - budsabangam, tanum (Interdisciplinary Journal of Humanities Studies, 2025)
The change in religious beliefs among the new generation youth in Thailand is an important issue in the present era, with significant social and cultural impacts, especially when compared to the rapid changes in the economy and technology. Today’s youth are influenced by various factors, such as access to diverse information through digital media, open education and knowledge, and societal changes that have shaped their perspectives differently from previous generations. Factors contributing to the changes in religious beliefs reflect an adaptation to contemporary circumstances. Thai youth today are more open to receiving religious information and adjusting their attitudes in ways that fit their daily lives. Some groups are turning to new religions that are not the dominant faiths in Thailand, which have emerged in the online world. Meanwhile, other groups of youth have chosen not to adhere to any religion at all, instead focusing on spiritual concepts or self-development through personal practices. The changes in religious beliefs among youth also reflect broader social and cultural shifts. These changes are not only a result of societal and technological changes but also a consequence of the intellectual development of youth, who now have broader and more flexible perspectives. The change in religious beliefs among Thailand’s new generation youth is a complex and multifaceted process, demonstrating their adaptability and their search for new meaning in life in a rapidly changing society. It reflects the development of Thai society, which is increasingly diverse in terms of religions and beliefs, and may serve as a guide to promote understanding and acceptance of religious diversity in the future.